Biomarker Research and Development for Coronavirus Disease 2019 (COVID-19): European Medical Research Infrastructures Call for Global Coordination. (22nd October 2020) - Oldoni, Emanuela; van Gool, Alain; García Bermejo, Laura; Scherer, Andreas; Mayrhofer, Michaela Th; Florindi, Francesco; Demotes, Jacques; Kubiak, Christine; Fauvel, Anne-Charlotte; Bietrix, Florence; Ussi, Anton; Andreu, Antonio L
Abstract: An effective response to the coronavirus disease 2019 (COVID-19) pandemic requires a better understanding of the biology of the infection and the identification of validated biomarker profiles that would increase the availability, accuracy, and speed of COVID-19 testing. Here, we describe the strategic objectives and action lines of the European Alliance of Medical Research Infrastructures (AMRI), established to improve the research process and tackle challenges related to diagnostic tests and biomarker development. Recommendations include: the creation of a European taskforce for validation of novel diagnostic products, the definition and promotion of criteria for COVID-19 samples biobanking, the identification and validation of biomarkers as clinical endpoints for clinical trials, and the definition of immune biomarker signatures at different stages of the disease. An effective management of the COVID-19 pandemic is possible only if there is a high level of knowledge and coordination between the public and private sectors within a robust quality framework. Abstract : Oldoni et al debate relevant issues related to coronavirus disease 2019 testing and biomarker development. European Medical Research Infrastructures call for a high level of knowledge and coordination between public and private sectors, likewise for quality and reproducibility along the research pipeline.